Effects of pharmacologic sclerostin inhibition or testosterone administration on soleus muscle atrophy in rodents after spinal cord injury. - Ean G Phillips; Luke A Beggs; Fan Ye; Christine F Conover; Darren T Beck; Dana M Otzel; Payal Ghosh; Anna C F Bassit; Stephen E Borst; Joshua F Yarrow (PLoS ONE)
Sclerostin is a circulating osteocyte-derived glycoprotein that negatively regulates Wnt-signaling after binding the LRP5/LRP6 co-receptors. Pharmacologic sclerostin inhibition produces bone anabolic effects after spinal cord injury (SCI), however, the effects of sclerostin-antibody (Scl-Ab) on muscle morphology remain unknown. In comparison, androgen administration produces bone antiresorptive effects after SCI and some, but not all, studies have reported that testosterone treatment ameliorates skeletal muscle atrophy in this context. Our purposes were to determine whether Scl-Ab prevents hindlimb muscle loss after SCI and compare the effects of Scl-Ab to testosterone enanthate (TE), an agent with known myotrophic effects. Male Sprague-Dawley rats aged 5 months received: (A) SHAM surgery (T8 laminectomy), (B) moderate-severe contusion SCI, (C) SCI+TE (7.0 mg/wk, im), or (D) SCI+Scl-Ab (25 mg/kg, twice weekly, sc). Twenty-one days post-injury, SCI animals exhibited a 31% lower soleus mass in comparison to SHAM, accompanied by >50% lower soleus muscle fiber cross-sectional area (fCSA) (p<0.01 for all fiber types). Scl-Ab did not prevent soleus atrophy, consistent with the relatively low circulating sclerostin concentrations and with the 91-99% lower LRP5/LRP6 gene expressions in soleus versus tibia (p<0.001), a tissue with known anabolic responsiveness to Scl-Ab. In comparison, TE partially prevented soleus atrophy and increased levator ani/bulbocavernosus (LABC) mass by 30-40% (p<0.001 vs all groups). The differing myotrophic responsiveness coincided with a 3-fold higher androgen receptor gene expression in LABC versus soleus (p<0.01). This study provides the first direct evidence that Scl-Ab does not prevent soleus muscle atrophy in rodents after SCI and suggests that variable myotrophic responses in rodent muscles after androgen administration are influenced by androgen receptor expression.